PENGEMBANGAN MEDIA POWERPOINT INTERAKTIF BERBANTUAN GAME BASED LEARNING UNTUK MENINGKATKAN SEMANGAT BELAJAR BAHASA INDONESIA SISWA KELAS VI SD NEGERI 3 KAMPUNG BARU - Made Ayu Diah Puspita Sari; I Made Suweta; IG Agung Jaya Suryawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the design, test the validity, measure the practicality, and determine the effectiveness of Interactive PowerPoint learning media assisted by Game Based Learning (GBL) in increasing the enthusiasm for learning Indonesian language for sixth grade students of SD Negeri 3 Kampung Baru. Using the Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), data was collected through questionnaires, interviews, and documentation. The results of the study showed that: (1) The media was successfully developed by integrating the PowerPoint, Canva, and Zep Quiz platforms; (2) Expert validation stated that the product was Very Valid with an average score from media experts of 97%, material experts 93%, and language experts 94%; (3) The media was considered Very Practical with a percentage of teacher responses of 100% and student responses of 93%; (4) The media was proven to be Effective in significantly increasing students' enthusiasm for learning based on the results of the Paired Sample t-Test with a significance value of 0.000 <0.05. It can be concluded that the interactive PowerPoint learning media supported by GBL is valid, practical, and effective for use in Indonesian language learning in elementary schools.